The first mono anthraquinone substituted monospiro cyclotriphosphazene derivatives and their effects on non-small cell lung cancer cells - ciftci, Gonuel Yenilmez; Bayik, Nagihan; Turhal, Gulseren; Baslilar, Izel Nermin; Demiroğlu-Zergeroğlu, Asuman (Elsevier Science Sa, 2022)
Cancer is a lethal disease with uncontrolled division and proliferation of cells under the influence of genetic and environmental conditions. The resistance of tumor cells to currently used drugs and their high-level side effects require the development of alternative agents. Since their discovery, anthraquinones have become invaluable as lead compounds in the development of anticancer drugs. Likewise, the cyclotriphosphazenes are a noble platform for the binding of the anthraquinone compounds. In this research, new anthraquinone substituted cyclotriphosphazenes (7-9) were synthesized and fully characterized by FT-IR, MALDI-TOF MS, 1H and 31P NMR spectroscopy. Successively, the effect of the phosphazene compounds was investigated on Non-Small Cell Lung Carcinoma (NSCLC) cell lines and non-tumoral mesothelial cells (MeT-5A). Our results indicated that compared to others, compound 8 was the most effective compound to reduce the viability of cancer cells and to induce apoptosis. Besides, compound 8 has showed selectivity to cancer cells rather than normal counterpart.
Keywords: Cyclotriphosphazene; Anthraquinone; NMR; Cytotoxicity; NSCLC